Artificial intelligence-powered precision: Unveiling the tumor microenvironment for a new frontier in personalized cancer therapy - Songwei Feng; Xia Yin; Yang Shen (Intelligent Medicine)
The tumor microenvironment (TME) is a pivotal determinant of cancer progression and therapeutic response. The advent of individualized tumor therapy, based on the in-depth analysis of the TME, represents a revolutionary transformation in oncology. Artificial intelligence (AI) provides unparalleled capabilities to analyze and decipher the complexities of the TME through multi-omics integration, spatial modeling, and predictive analytics. By combining computational innovations with clinical insights, AI is driving a new paradigm in precision medicine. This editorial explores the transformative potential of AI in individualized tumor therapy, highlighting the groundbreaking applications and strategic directions to advance this field.